Assessing User Experience of Online Doctor Services in Halodoc, Good Doctor, and Alodokter Using the System Usability Scale (SUS) - Roma Firmansyah; Deni Luvi Jayanto (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to evaluate the usability level of online doctor consultation features in three popular digital health applications in Indonesia, namely Halodoc, Good Doctor, and Alodokter. The method used is a descriptive quantitative approach with the System Usability Scale (SUS) instrument. A total of 45 respondents were selected purposively and asked to try each application, then provide assessments through the SUS questionnaire. The research results show that Good Doctor obtained the highest average score of 83.56 (Grade A), followed by Alodokter with a score of 81.33 (Grade A), and Halodoc with 77.89 (Grade B+). These findings indicate that Good Doctor and Alodokter have excellent usability levels, while Halodoc is categorized as good but still requires improvement, particularly in aspects of learnability and error recovery. An alysis was also conducted using additional approaches such as percentile ranking, grade categories, acceptability ranges, and Net Promoter Score (NPS). The results of this study emphasize the importance of user-centered design in developing digital health services and support the use of SUS as a practical and reliable evaluation tool. These findings are expected to provide input for application developers in improving service quality and user satisfaction.